Gender difference of geographic distribution of physicians in Japan: three-point analysis of 1994, 2004 and 2014 - Kazuki Kimura; Kazuo Inoue; Takahito Ando; Masanori Ito (BMC, 2023)
Abstract Background Japan's medical education system produces 9,000 graduates annually. Despite the government's implementation of several strategies, including increasing the number of doctors trained, the country still struggles with a shortage of physicians in rural areas. This study examined this issue, focusing on gender and considering years of physician experience, demographic and geographic factors. Methods We analyzed the Physician Census from 1994, 2004, and 2014, examining data on physicians' gender and the number of years since licensure. To correct the impact of municipal mergers, the analysis was aligned with the number of municipalities in 2014 (1741). We examined data from each physician (gender and years of medical experience) and analyzed the demographic and geographic distribution trend using Spearman correlation coefficients. We then used the Gini coefficient to evaluate the distribution change of physicians based on gender and years of experience. Results The number of physicians increased 1.29-fold over the 20-year observation period (1.23-fold for male physicians and 2.17-fold for female physicians), and the percentage of female physicians increased from 13.4% to 20.4%. We found that 87.7% of physicians were concentrated in the top 1/3 municipalities in terms of population. The number of female physicians was higher at 91.8% compared to 86.8% for male physicians. The Gini coefficients were lower for veteran physicians of both sexes than for younger physicians. The Gini coefficient for all physicians was 0.315-0.298-0.298 (male physicians: 0.311-0.289-0.283, female physicians: 0.394-0.385-0.395) The Gini coefficients for female compared to male physicians were higher in all age groups, showing that The distribution of female physicians is skewed toward urban areas. Conclusion Female physicians are less distributed in rural areas than male physicians. In addition, despite the fact that the number of female physicians has increased more than male physicians over the past 20 years, the geographic ubiquity of female physicians has not improved. Since the trend of increasing the number of female physicians is expected to continue in the future, it is necessary to take some measures, such as providing a work-life balance suitable for female physicians.